Origin of the Bunun Indigenous People of Taiwan, a Review of Published Material Using Y-Chromosome and Mitochondrial DNA Gene Systems - Jean A. Trejaut (DNA, 2022)
Anthropological and linguistic studies place the first settlement of Austronesian speaking Taiwanese (AN_Tw) in the mid-Holocene era. However, geneticists have revealed exclusive diversity among the Bunun indigenous people, implying that their ancestral origin needs further study. The mitochondrial DNA (mtDNA) polymorphism of the Bunun shows a homogeneous relationship with other AN_Tw. However, the Y-chromosome polymorphism shows two major haplogroups, O1a2-M50 (60.7%), also seen to a lesser extent among the Northern AN_Tw, and O1b1a1a1a1a1-M88 (37.5%), scarce among all other AN and non-AN groups in Taiwan, but prevailing in Southeast Asia (SEA) and Mainland Southeast Asia (MSEA). While the present-day mtDNA profile of the Bunun typifies the long-term demographic standard for all AN_Tw since the Neolithic era, their Y-chromosome profile suggests an arrival of male settlers in the last two to three millennia from SEA or MSEA, who mixed exclusively with the Bunun indigenous people.